Akuntabilitas Publik Pada Pengelolaan Zakat Mal Sebagai Solusi Pengentasan Kemiskinan - yuliastuti, rika (Universitas Muhammadiyah Metro, 2023)
This research takes the title Public Accountability in Zakat Mal Management as a Solution for Poverty Alleviation. The background of this research is the problem of poverty which is still a serious problem in Indonesia. And even though various programs have been implemented in an effort to solve the problem of poverty, it seems as if the problem of poverty has never been resolved.The aim of the research is to determine public accountability and the impact of zakat mal on poverty alleviation in Indonesia. The method used is a descriptive qualitative method approach and content analysis techniques.From studies conducted on various literature and analyzing existing data, it can be seen that there is a positive influence between the distribution of zakat mal and poverty alleviation in many areas in Indonesia. Several areas that distribute zakat malls are able to reduce poverty levels. This shows that effective distribution of zakat mal can help reduce poverty in Indonesia. The portrait of public accountability and the success of poverty alleviation programs was also seen in the government of Umar bin Abdul Aziz in the Umayyad era, when there were no longer any people willing to accept the distribution of zakat mal assets because people felt they no longer had the right to these assets. The government of Umar bin Abdul Aziz's era was able to completely eradicate poverty and poverty in just a short period of government, namely three years.